Sustainable Tourism Implementation in the Matahari Terbit Beach Area: Perspectives of Tourists, Business Actors, and Local Communities - I Made Weda Satia Negara; Atabuy Frit Elisa Yonce; Maria Suriati Sana (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study aims to analyze the implementation of sustainable tourism and to identify the perceptions of tourists, tourism business operators, and local communities in the Matahari Terbit Beach area, Sanur. Method: The research employs a qualitative approach with a descriptive design to obtain an in-depth understanding of the phenomenon from the perspectives of key stakeholders. Data were collected through direct observation, semi-structured interviews, documentation, and literature review. A total of 15 informants—comprising tourists, business operators, and local community members—were selected using purposive sampling. Data analysis was conducted using an interactive model, including data reduction, data display, and conclusion drawing, supported by triangulation and member checking to ensure validity Result: The findings reveal that the implementation of sustainable tourism in the study area has not been fully optimized. Tourists generally demonstrate limited understanding of sustainability, mainly focusing on environmental aspects. Tourism business operators tend to adopt a pragmatic approach by prioritizing economic benefits. Meanwhile, local communities exhibit more complex perceptions, as they experience both the positive and negative impacts of tourism development. These differing perspectives contribute to a lack of synergy among stakeholders in supporting sustainable tourism practices. Contribution: This study highlights the critical need for stronger collaboration among stakeholders, enhanced sustainability education, and more robust regulatory frameworks. It contributes to the existing body of knowledge by demonstrating how differing stakeholder perceptions can hinder the effective implementation of sustainable tourism. The findings provide practical insights for policymakers, tourism planners, and researchers to develop more integrated and balanced strategies that align environmental, socio-cultural, and economic dimensions in destination management.